2022
DOI: 10.21037/tau-22-423
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic artery occlusion: initial findings on pathophysiological response in a canine prostate model

Abstract: Background: Prostatic artery embolization (PAE) is an alternative treatment for symptomatic benign prostatic hyperplasia (BPH) in men. A technical modification of conventional PAE has been developed in a canine prostate model consisting of prostatic artery occlusion (PAO) using Onyx ® whose therapeutic effect is prostate shrinkage. However, the underlying mechanisms are not well clarified. The purpose was to evaluate the biological mechanisms responsible for therapeutic effects of PAO in the canine prostate.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…To study this point, other teams have assessed embolization with another liquid agent, N-Butyl Cyanoacrylate Glue, and showed the same clinical efficacy as with microparticles, with no more complications and shorter duration of embolizations, therefore less X-rays exposition (12). However, Lucas-Cava et al showed on angiographic controls at 6 months that, despite an initial complete occlusion by the liquid agent, either the prostatic arteries had repermeabilized or the prostate had recruited other arteries, highlighting the limits of this new technique (8). In addition, studies on repeated embolizations of prostatic arteries showed much lower efficacy, suggesting another unresolved mechanism at stake in the treatment of prostates possibly resistant to ischemia (10,11).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…To study this point, other teams have assessed embolization with another liquid agent, N-Butyl Cyanoacrylate Glue, and showed the same clinical efficacy as with microparticles, with no more complications and shorter duration of embolizations, therefore less X-rays exposition (12). However, Lucas-Cava et al showed on angiographic controls at 6 months that, despite an initial complete occlusion by the liquid agent, either the prostatic arteries had repermeabilized or the prostate had recruited other arteries, highlighting the limits of this new technique (8). In addition, studies on repeated embolizations of prostatic arteries showed much lower efficacy, suggesting another unresolved mechanism at stake in the treatment of prostates possibly resistant to ischemia (10,11).…”
mentioning
confidence: 95%
“…Lucas-Cava et al studied the effects of PAE on a canine model (8). They described a new technique of embolization with a complete occlusion of the prostatic arteries by a liquid agent, ethylene-vinyl alcohol copolymer or Onyx ® , an agent originally used for the embolization of vascular malformations (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation